Principal Leadership Function on Teacher Performance for Secondary Schools - M. Said Saggaf; Denok Sunarsi; Hariyaty Ab Wahid; Dodi Ilham; Achmad Rozi (Har Press Indonesia, 2021)
Education is a fundamental factor that determines the quality of the human development index in any country. Leadership plays an essential role in many organizations, including educational organizations. Principals determine how education fosters and how teachers improve and develop students. Several factors could influence how a principal leads and manages subordinates. The principal's leadership function covers many excellent leadership functions within the educational system, including the educational administrator, educational supervisor, and educational leader. This study employed a quantitative research approach. Forty teachers participated as respondents in this research. The results showed that teachers' performance in the teaching and learning process was in the category of